Role of personality disorder in randomised controlled trials of pharmacological interventions for adults with mood disorders: a protocol for a systematic review and meta-analysis - Kavanagh, Bianca E (BMJ Open, 2019)
INTRODUCTION: Remission rates for mood disorders, including depressive and bipolar disorders, remain relatively low despite available treatments, and many patients fail to respond adequately to these interventions. Evidence suggests that personality disorder may play a role in poor outcomes. Although personality disorders are common in patients with mood disorders, it remains unknown whether personality disorder affects treatment outcomes in mood disorders. We aim to review currently available evidence regarding the role of personality disorder on pharmacological interventions in randomised controlled trials for adults with mood disorders. METHODS AND ANALYSIS: A systematic search of Cochrane Central Register of Controlled Clinical Trials (CENTRAL) via cochranelibrary.com, PubMed via PubMed, EMBASE via embase.com, PsycINFO via Ebsco and CINAHL Complete via Ebsco databases will be conducted to identify randomised controlled trials that have investigated pharmacological interventions in participants aged 18 years or older for mood disorders (ie, depressive disorders and bipolar spectrum disorders) and have also included assessment of personality disorder. One reviewer will screen studies against the predetermined eligibility criteria, and a second reviewer will confirm eligible studies. Data will be extracted by two independent reviewers. Methodological quality and risk of bias will be assessed using the Cochrane Risk of Bias tool. A systematic review, and if sufficient evidence is identified, a meta-analysis will be completed. Meta-analysis will be conducted using the standardised mean difference approach and reported with 95% CIs. A random effects model will be employed and statistical heterogeneity will be evaluated using the I(2) statistic. Prespecified subgroup analyses will be completed. ETHICS AND DISSEMINATION: As this systematic review will use published data, ethics permission will not be required. The outcomes of this systematic review will be published in a relevant scientific journal and presented at a research conference. TRIAL REGISTRATION NUMBER: CRD42018089279.